Aspek Biologi dan Pemetaan Daerah Penangkapan Lobster (Panulirus spp) di Perairan Kampung Akudiomi Distrik Yaur Kabupaten Nabire - Bayu Pranata; Vera Sabariah; Suhaemi Suhaemi (Jurnal Sumberdaya Akuatik Indopasifik, 2017)
This research was done on March-April 2014 at village of Akudiomi that was wellknown as Kwatisore in Nabire Regency at Papua Province. The research aimed to determine species composition, length-weigh relationship, local fishermen inventarization and mapping lobster fishing ground. Method used was descriptive with observation techniqu, sampling and interview. Also, the mapping and identification the correlation between physical oceanography parameters (temperature, salinity, depth and pH) on the fishing ground of lobster was to know the effect on the lobster availability. Resuls showed that during field observation, three species of lobsters were caught by fisheremen in Akudiomi that are P. versicolor for 111 individu, P. longipes and Thenus spp was 1 individu consecutively. The prediction of lobster growth pattern only done for P. versicolor as the dominant species caught in Akudiomi, that P. versicolor’ carapace length 8-13 and weight 250-1,097 gr/individu. Correlation between carapace length and weight of P.versicolor indicated positive with the same direction at 0.8636, (near 1). Analysis growth pattern P. versicolor showed , thus means or allometric negative (the growth of length faster than weight). Regression analysis indicated that temperature, depth, salinity and pH significantly affected the yield of lobster caught by fishermen in Akudiomi. Morevoer, oseanography aspects that had significant effect to caught of lobster temperature, salinity and pH.